Two parallel pathways for ferric and ferrous iron acquisition support growth and virulence of the intracellular pathogen Francisella tularensis Schu S4. Issue 3 (25th February 2016) - Pérez, Natalie; Johnson, Richard; Sen, Bhaswati; Ramakrishnan, Girija
Abstract: Iron acquisition mechanisms in Francisella tularensis, the causative agent of tularemia, include the Francisella siderophore locus ( fsl) siderophore operon and a ferrous iron–transport system comprising outer‐membrane protein FupA and inner‐membrane transporter FeoB. To characterize these mechanisms and to identify any additional iron uptake systems in the virulent subspecies tularensis, single and double deletions were generated in the fsl and feo iron acquisition systems of the strain Schu S4. Deletion of the entire fsl operon caused loss of siderophore production that could be restored by complementation with the biosynthetic genes fslA and fslC and Major Facilitator Superfamily (MFS) transporter gene fslB . 55 Fe‐transport assays demonstrated that siderophore‐iron uptake required the receptor FslE and MFS transporter FslD. A Δ feoB ′ mutation resulted in loss of ability to transport ferrous iron ( 55 Fe 2+ ). A Δ feoB ′ Δ fslA mutant that required added exogenous siderophore for growth in vitro was unable to grow within tissue culture cells and was avirulent in mice, indicating that no compensatory cryptic iron uptake systems were induced in vivo. These studies demonstrate that the fsl and feo pathways function independently and operate in parallel to effectively support virulence of F. tularensis . Abstract : We have examined the mechanisms that mediate iron acquisition in the Gram‐negative Francisella tularensis strain SchuS4 and demonstrate that it possesses only two parallel pathways of siderophore‐mediated ferric iron acquisition and ferrous iron transport. These specialized mechanisms involving high‐affinity outer‐membrane transporters adequately support growth and full virulence of this intracellular pathogen.